2009
DOI: 10.1021/jm900843g
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Human Immunodeficiency Virus Type 1 (HIV-1) Attachment. 5. An Evolution from Indole to Azaindoles Leading to the Discovery of 1-(4-Benzoylpiperazin-1-yl)-2-(4,7-dimethoxy-1H-pyrrolo[2,3-c]pyridin-3-yl)ethane-1,2-dione (BMS-488043), a Drug Candidate That Demonstrates Antiviral Activity in HIV-1-Infected Subjects

Abstract: Azaindole derivatives derived from the screening lead 1-(4-benzoylpiperazin-1-yl)-2-(1H-indol-3-yl)ethane-1,2-dione (1) were prepared and characterized to assess their potential as inhibitors of HIV-1 attachment. Systematic replacement of each of the unfused carbon atoms in the phenyl ring of the indole moiety by a nitrogen atom provided four different azaindole derivatives that displayed a clear SAR for antiviral activity and all of which displayed marked improvements in pharmaceutical properties. Optimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
90
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 50 publications
1
90
0
Order By: Relevance
“…However, BMS-378806 failed to achieve targeted plasma exposures in humans. Therefore, a related compound, BMS-488043, with improved in vitro antiviral activity and pharmacokinetic properties was advanced into clinical development (1,23,30,33). Taken with a high-fat meal, BMS-488043 achieved a 10-fold higher concentration in the plasma of human subjects than was observed for BMS-378806.…”
mentioning
confidence: 99%
“…However, BMS-378806 failed to achieve targeted plasma exposures in humans. Therefore, a related compound, BMS-488043, with improved in vitro antiviral activity and pharmacokinetic properties was advanced into clinical development (1,23,30,33). Taken with a high-fat meal, BMS-488043 achieved a 10-fold higher concentration in the plasma of human subjects than was observed for BMS-378806.…”
mentioning
confidence: 99%
“…It is in phase II clinical development. In a preliminary clinical study, BMS-488043 administered as monotherapy for 8 days demonstrated potent antiviral activity [17]. Pfizer Inc. has two compounds (WO-2005016344 and WO-2005121094) with similar characteristics to BMS-488043.…”
Section: Cd4 -Gp120 Binding Inhibitorsmentioning
confidence: 99%
“…Compound 1 blocks HIV-1-mediated cell-cell fusion and the formation of gp41 six-helix bundles, as does enfuvirtide [15]. Small-molecule CD4 mimics with oxalamide and related substructures are another series of anti-HIV agents [16][17][18]. The representative BMS-448043 (2) exhibits subnanomolar anti-HIV activity by interaction with the CD4 binding pocket in gp120 [18].…”
Section: Introductionmentioning
confidence: 99%
“…Small-molecule CD4 mimics with oxalamide and related substructures are another series of anti-HIV agents [16][17][18]. The representative BMS-448043 (2) exhibits subnanomolar anti-HIV activity by interaction with the CD4 binding pocket in gp120 [18]. Alternatively, there are some examples of antagonists against CXC chemokine receptor type 4 (CXCR4).…”
Section: Introductionmentioning
confidence: 99%